Regeneration method and application of silicon-carbon negative electrode material of waste lithium ion battery

Through a series of chemical and physical treatment steps, the silicon carbon anode material of waste lithium-ion batteries is successfully converted into high-quality recycled materials, solving the stability and difficulty of recycling of materials during the circulation process, achieving efficient regeneration and recycling of materials, and promoting the sustainable development of the battery industry.

CN119706825AActive Publication Date: 2025-03-28ZHEJIANG XINSHIDAI ZHONGNENG RECYCLING TECH CO LTD

Patent Information

Application Number
CN202411913338.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The silicon carbon anode material of waste lithium-ion batteries will expand in volume during the charge and discharge cycle, resulting in rupture and powderization, and it will be difficult to recycle and use, affecting the use of environment and resources.

Method used

By mixing the silicon-carbon negative electrode material of the used lithium-ion battery with alkaline substances, calcining under a non-oxidizing atmosphere, then washing and separating the graphite material and the silicon-containing solution, adjusting the pH to precipitate silicic acid, calcining to form sub-oxide, and forming a regenerated silicon-carbon negative electrode material through carbon coating treatment.

Benefits of technology

It has achieved efficient recycling and reuse of waste silicon-carbon anode materials, significantly improved the structural stability and electrochemical performance of the materials, reduced recycling costs, and promoted the sustainable development of the lithium-ion battery industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706825A_ABST
    Figure CN119706825A_ABST
Patent Text Reader

Abstract

The invention discloses a waste lithium ion battery silicon-carbon negative electrode material regeneration method and application thereof, and the method comprises the following steps: S1, mixing a waste lithium ion battery silicon-carbon negative electrode material with an alkaline substance, and calcining in a non-oxidizing atmosphere to obtain a calcined mixture; s2, washing the calcined mixture to be neutral, and performing solid-liquid separation to obtain a graphite material and a silicon-containing solution; s3, adjusting the pH value of the silicon-containing solution to a level at which silicate is precipitated, reacting under heating, carrying out solid-liquid separation, and collecting silicic acid precipitate; s4, mixing the silicic acid precipitate with a silicon simple substance, grinding the mixture into micron-scale powder, calcining the micron-scale powder under a vacuum condition, and collecting generated silicon monoxide; and S5, carrying out carbon coating treatment on silicon monoxide and the graphite material prepared in the step S2 to obtain the regenerated silicon-carbon negative electrode material. According to the scheme, the waste silicon-carbon negative electrode material is successfully converted into a high-quality regenerated material, and the material can be directly applied to production and manufacturing of new batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries and applications thereof. Background Art

[0002] Lithium-ion batteries have been widely and deeply used in many fields such as electric vehicles, portable electronic devices, and energy storage systems due to their significant advantages such as high energy power density, excellent cycle stability, high operating voltage, outstanding safety performance, and environmental friendliness. However, as consumable products, lithium-ion batteries inevitably have a certain service life limit. As their service life gradually runs out, if a large number of scrapped batteries are not properly handled and recycled, the harmful substances contained in them may leak into the environment, posing a serious threat to soil, water sources, and ecosystems, and thus affecting human health.

[0003] At the same time, key materials such as lithium, cobalt, copper, and silicon-carbon contained in waste lithium batteries have shown extremely high recycling value at a time when global resources are becoming increasingly scarce. These materials are not only important raw materials necessary for the manufacture of new batteries, but also can significantly reduce the demand for mining of primary resources, reduce energy consumption and environmental pollution through recycling. Therefore, scientific and effective management and disposal of waste lithium batteries can not only effectively alleviate the pressure on the environment and protect the ecological environment, but also realize the recycling of resources, bringing significant environmental and economic benefits.

[0004] At present, the main focus of recycling waste lithium batteries is on the positive electrode materials and the metal elements therein, while there is relatively little research on the silicon-carbon materials of the negative electrode. Silicon-carbon materials have shown great application potential in high-energy lithium-ion batteries because of their theoretical capacity of up to 4200mAh / g and a low platform potential of 0.5V. However, silicon-carbon materials will undergo significant volume expansion during the charge and discharge cycle, causing the negative electrode materials to crack or even pulverize after long-term cycling. This will not only destroy the structural stability of the battery, but also form a thick solid electrolyte interface (SEI) film on the surface of the negative electrode material, further hindering the transmission of lithium ions and resulting in a large loss of silicon and lithium elements. At the same time, during the battery cycle and disassembly process, silicon-carbon negative electrode materials may also deposit and adsorb other metal elements, increasing the difficulty of recycling.

[0005] Therefore, the collected waste silicon-carbon anode materials need to be further processed using advanced processing technology to restore their original performance and quality. This not only helps to meet the requirements of recycling and reuse of silicon-carbon anode materials and improve resource utilization, but also reduces the negative impact of waste batteries on the environment and promotes the sustainable development of the lithium-ion battery industry. However, there are few related reports in the prior art. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries, by which the silicon-carbon negative electrode materials can be effectively regenerated.

[0007] The present invention also proposes the application of the above method.

[0008] According to the first aspect of the present invention, the method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries comprises the following steps:

[0009] S1. Mixing the silicon-carbon negative electrode material of waste lithium-ion batteries with an alkaline substance, and calcining the mixture in a non-oxidizing atmosphere to obtain a calcined mixture;

[0010] S2, washing the calcined mixture until it is neutral, and separating the solid from the liquid to obtain a graphite material and a silicon-containing solution;

[0011] S3, adjusting the pH of the silicon-containing solution to a level that causes silicate precipitation, reacting under heating, separating the solid from the liquid, and collecting the silicic acid precipitate;

[0012] S4, mixing the silicic acid precipitate with silicon element, grinding into micrometer-sized powder, calcining under vacuum conditions, and collecting the generated silicon oxide;

[0013] S5. Carbon-coating the silicon monoxide and the graphite material obtained in step S2 to obtain a regenerated silicon-carbon negative electrode material.

[0014] According to the preparation method of the embodiment of the present invention, at least the following beneficial effects are achieved: the present invention proposes an innovative solution, which cleverly recovers and reuses waste silicon-carbon negative electrode materials through a series of chemical and physical treatment steps. The solution first mixes the waste silicon-carbon negative electrode materials with an alkaline substance and calcines them under non-oxidizing atmosphere conditions. This step not only helps to effectively remove impurities in the material, but also partially changes its structure, laying a solid foundation for subsequent treatment. During the calcination process, the silicon component is converted into silicate. Subsequently, the graphite material can be easily separated from the silicon-containing solution by a simple water immersion treatment. Further, by adjusting the pH value of the silicon-containing solution, a silicic acid precipitate can be precipitated. The precipitation reaction is carried out under heating conditions. By increasing the temperature of the reaction system, hydrolysis can be promoted, the reaction rate can be accelerated, the reaction can be more thorough, and the product can be accelerated to condense from a colloidal substance into a precipitate, accelerating the aging process, so as to facilitate subsequent filtration and separation. The silicic acid precipitate is calcined together with silicon element to generate silicon oxide. The entire treatment process is easy to operate and does not require the introduction of too many complex reagents, but it successfully achieves the effective separation and reuse of silicon and carbon, significantly simplifies the recycling process and improves economic benefits.

[0015] Another highlight of the present invention is that, through the ingenious combination of various steps, silicon and lithium elements are recovered from waste materials and reintegrated into new silicon-carbon negative electrode materials. At the same time, the recovered graphite material is directly used for carbon coating, which maximizes the recovery and utilization of useful components in the material. In particular, the recovered graphite material is reused to coat the surface of silicon oxide particles to form a protective layer. This protective layer not only effectively alleviates the volume expansion problem of silicon and prevents the cracking and pulverization of the negative electrode material, but also significantly enhances the overall structural stability of the material, enabling it to maintain excellent performance during long-term cycles.

[0016] In summary, the scheme of the present invention successfully converts waste silicon-carbon negative electrode materials into high-quality recycled materials through a series of carefully designed chemical and physical treatment steps. This recycled material can be directly used in the production and manufacturing of new batteries, which not only reduces the difficulty and cost of recycling, but also realizes the efficient regeneration and recycling of materials, which is of great significance for promoting the sustainable development of the battery industry.

[0017] According to some embodiments of the present invention, the alkaline substance in step S1 includes at least one of an alkali metal base or an alkali metal carbonate.

[0018] According to some embodiments of the present invention, the alkaline substance in step S1 includes at least one of sodium hydroxide, lithium hydroxide or sodium carbonate.

[0019] According to some embodiments of the present invention, in step S1, the mass ratio of the silicon-carbon negative electrode material of the waste lithium-ion battery to the alkaline substance is 5:1 to 5:6.

[0020] According to some embodiments of the present invention, the non-oxidizing atmosphere comprises at least one of carbon dioxide, nitrogen or an inert gas.

[0021] According to some embodiments of the present invention, in step S1, the calcination temperature is 300° C. to 700° C.; and / or the calcination time is 4 to 5 hours.

[0022] According to some embodiments of the present invention, the washing in step S2 is water washing.

[0023] According to some embodiments of the present invention, the water washing is performed 3 to 5 times.

[0024] According to some embodiments of the present invention, during the water washing process, the liquid-to-solid ratio of water to the calcined mixture is 4:1 to 8:1.

[0025] According to some embodiments of the present invention, in step S3, the pH is adjusted to 1.5-3.0.

[0026] According to some embodiments of the present invention, acid is used to adjust the pH in step S3.

[0027] According to some embodiments of the invention, the acid is sulfuric acid, hydrochloric acid or nitric acid solution.

[0028] According to some embodiments of the present invention, the concentration of the sulfuric acid solution is 1 mol / L to 2.5 mol / L, the concentration of the hydrochloric acid solution is 1 mol / L to 4 mol / L, and the concentration of the nitric acid solution is 1 mol / L to 2 mol / L. Hydrochloric acid and nitric acid are easily volatile under heating conditions, so sulfuric acid is preferably used.

[0029] According to some embodiments of the present invention, the heating temperature in step S3 is 70-90°C.

[0030] According to some embodiments of the present invention, in step S4, the silicic acid precipitate is mixed with silicon element in a molar ratio of 1:0.8 to 1:1.2.

[0031] According to some embodiments of the present invention, in step S4, the calcination temperature is 1200-1800°C.

[0032] According to some embodiments of the present invention, in step S4, the calcination time is 4 to 5 hours.

[0033] According to some embodiments of the present invention, in step S5, the silicon monoxide and the graphite material are mixed in a mass ratio of 10:1 to 10:1.4.

[0034] According to some embodiments of the present invention, in step S5, the carbon coating treatment operation includes sintering, and the sintering conditions include at least one of the following conditions:

[0035] 1) Sintering in a CVD atmosphere furnace (chemical vapor deposition atmosphere furnace);

[0036] 2) The sintering temperature is 1000-1200°C;

[0037] 3) The sintering time is 8 to 10 hours.

[0038] Carbon coating can provide better electronic conductivity and reduce the formation of SEI film, thereby improving the transmission efficiency of lithium ions. The use of CVD furnace can accurately control the reaction conditions such as temperature, gas flow, reaction time, etc., so as to achieve precise control of the thickness, structure and properties of the carbon coating layer.

[0039] The application of the embodiment according to the second aspect of the present invention includes the application of the above method in the preparation of lithium-ion batteries.

[0040] According to the application of the embodiment of the present invention, there are at least the following beneficial effects: the lithium-ion battery negative electrode material regeneration method of the present invention has shown broad application prospects in the field of preparation and recycling of lithium-ion batteries. The method significantly reduces costs by optimizing the regeneration process, while improving the overall economic benefits. Specifically, it can not only effectively recycle silicon, lithium, graphite, etc. in waste lithium-ion battery negative electrode materials, but also achieve efficient reuse of these materials through innovative regeneration technology, thereby significantly reducing the cost of raw materials while ensuring battery performance. In addition, the method also pays attention to environmental protection and sustainability, reduces waste emissions, conforms to the development trend of green manufacturing, and further enhances its market competitiveness and economic benefits. Therefore, the lithium-ion battery regeneration method of the present invention is not only cost-effective, but also provides strong support for the sustainable development of the lithium-ion battery industry.

[0041] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0043] Figure 1 is a SEM image of the collected waste silicon-carbon negative electrode material before being processed in Example 1 of the present invention;

[0044] Figure 2 This is a SEM image of the regenerated silicon-carbon negative electrode material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0046] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0047] The silicon-carbon negative electrode materials of waste lithium-ion batteries in the following embodiments are from the same source, and all parameter indicators are consistent.

[0048] Example 1

[0049] This example provides a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries and its application. The specific operation of the regeneration method is as follows:

[0050] (1) Collect the waste silicon-carbon negative electrode material (SEM image of which is shown in Figure 1 The flaky sodium hydroxide solid was mixed uniformly in a mass ratio of 5:5, and calcined at a high temperature in a carbon dioxide atmosphere at a calcination temperature of 600° C. for 4 h to obtain a calcined mixture.

[0051] (2) The calcined mixture is washed with deionized water for multiple times at a liquid-to-solid ratio of 5:1 until it becomes neutral, and then filtered to obtain a graphite material for sintering to prepare a negative electrode material for a lithium-ion battery and a silicon-containing leaching solution.

[0052] (3) The pH of the silicon-containing leaching solution was adjusted to 1.5 with 1 mol / L sulfuric acid solution, and the reaction temperature was 80°C to completely precipitate the silicate. The silicic acid precipitate was filtered and dried.

[0053] (4) The silicic acid precipitate and silicon element are mixed evenly in a 1:1 molar ratio, ground into micrometer-sized powder, and calcined under vacuum conditions at a calcination temperature of 1600° C. for 4 hours. The generated gas is collected and cooled to obtain silicon dioxide solid.

[0054] (5) The silicon dioxide solid and the graphite material recovered in step (2) are subjected to carbon coating treatment, the silicon dioxide solid and the graphite material are mixed evenly in a mass ratio of 10:1.2, ground into micrometer-level powder, sintered in a CVD atmosphere furnace at a calcination temperature of 1200° C. for 10 h, and after the sintered product is naturally cooled to room temperature, it is sieved through a 300-mesh sieve to obtain a recycled product SiOx@C material.

[0055] The regenerated SiOx@C silicon carbon electrode was used as the working electrode, metallic lithium was used as the negative electrode, and the conductive agent, binder, and electrolyte (1 mol / L LiPF 6Dissolved in a 1:1:1 EC:DEC:DMC solvent) and a 2500-type separator were assembled into a button-type simulated battery in an argon-filled glove box (O 2 <0.01ppm, H 2 O<0.01ppm), constant current charge and discharge mode was used, and the cut-off voltage was 0.01-2.00V for electrochemical performance testing. The first reversible capacity of the material was 2450.4mAh / g. After 300 cycles at a current density of 1.0A / g, it still retained a reversible capacity of 2314.8mAh / g, and the capacity retention rate was 94.5%.

[0056] Example 2

[0057] This example provides a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries and its application. The difference between this method and Example 1 is that the type of alkaline substance is different. Specifically, the operation is as follows:

[0058] (1) The collected waste silicon-carbon negative electrode material and sodium carbonate solid are mixed evenly in a mass ratio of 5:5, and calcined at high temperature in a carbon dioxide atmosphere at a calcination temperature of 600° C. for 4 h to obtain a calcined mixture.

[0059] (2) The calcined mixture is washed with deionized water for multiple times at a liquid-to-solid ratio of 5:1 until it becomes neutral, and then filtered to obtain a graphite material for sintering to prepare a negative electrode material for a lithium-ion battery and a silicon-containing leaching solution.

[0060] (3) The pH value of the silicon-containing leaching solution was adjusted to 1.5 with 1 mol / L sulfuric acid solution, and the reaction temperature was 80°C to completely precipitate the silicate. The silicic acid precipitate was obtained by suction filtration and dried.

[0061] (4) Mix the silicic acid precipitate and silicon element in a 1:1 molar ratio, grind into micrometer-sized powder, and calcine under vacuum conditions at a calcination temperature of 1600°C for 4 hours. Collect the generated gas and cool it to obtain silicon dioxide solid.

[0062] (5) The silicon dioxide solid and the graphite material in step b) are subjected to carbon coating treatment, the silicon dioxide solid and the graphite material are mixed uniformly at a mass ratio of 10:1.2, ground into micron-sized powder, sintered in a CVD atmosphere furnace, the calcination temperature is 1200°C, the insulation time is 10 hours, and after the sintered product is naturally cooled to room temperature, it is passed through a 300-mesh sieve to obtain a recycled product SiOx@C material

[0063] The regenerated SiOx@C silicon-carbon electrode is used as the working electrode, the metal lithium is used as the negative electrode, and the conductive agent, the binder, the electrolyte (1 mol / L LiPF 6Dissolved in a 1:1:1 EC:DEC:DMC solvent) and a 2500-type separator were assembled into a button-type simulated battery in an argon-filled glove box (O 2 <0.01ppm, H 2 O<0.01ppm), constant current charge and discharge mode was used, and the cut-off voltage was 0.01-2.00V for electrochemical performance testing. The first reversible capacity of the material was 1650.9mAh / g. After 300 cycles at a current density of 1.0A / g, it still retained a reversible capacity of 1281.2mAh / g, and the capacity retention rate was 77.6%.

[0064] Example 3

[0065] This example provides a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries and its application. The difference between this method and Example 1 is that the type and concentration of the acid solution in step (3) are different.

[0066] (1) The collected waste silicon-carbon negative electrode material and the flaky sodium hydroxide solid are uniformly mixed in a mass ratio of 5:5, and calcined at high temperature in a carbon dioxide atmosphere at a calcination temperature of 600° C. for 4 hours to obtain a calcined mixture.

[0067] (2) The calcined mixture is washed with deionized water for multiple times at a liquid-to-solid ratio of 5:1 until it becomes neutral, and then filtered to obtain a graphite material for sintering to prepare a negative electrode material for a lithium-ion battery and a silicon-containing leaching solution.

[0068] (3) The pH value of the silicon-containing leaching solution was adjusted to 1.5 with a 2 mol / L hydrochloric acid solution, and the reaction temperature was 80° C. to completely precipitate the silicate, and the silicic acid precipitate was obtained by suction filtration and dried.

[0069] (4) The silicic acid precipitate and silicon element are mixed evenly in a 1:1 molar ratio, ground into micrometer-sized powder, and calcined under vacuum conditions at a calcination temperature of 1600° C. for 4 hours. The generated gas is collected and cooled to obtain silicon dioxide solid.

[0070] (5) The silicon dioxide solid and the graphite material in step b) are subjected to carbon coating treatment, the silicon dioxide solid and the graphite material are mixed evenly in a mass ratio of 10:1.2, ground into micrometer-level powder, sintered in a CVD atmosphere furnace at a calcination temperature of 1200° C. for 10 h, and after the sintered product is naturally cooled to room temperature, it is sieved through a 300-mesh sieve to obtain a recycled product SiOx@C material.

[0071] The regenerated SiOx@C silicon-carbon electrode is used as the working electrode, the metal lithium is used as the negative electrode, and the conductive agent, the binder, the electrolyte (1 mol / L LiPF 6Dissolved in a 1:1:1 EC:DEC:DMC solvent) and a 2500-type separator were assembled into a button-type simulated battery in an argon-filled glove box (O 2 <0.01ppm, H 2 O<0.01ppm), constant current charge and discharge mode was used, and the cut-off voltage was 0.01-2.00V for electrochemical performance testing. The first reversible capacity of the material was 1982.2mAh / g. After 300 cycles at a current density of 1.0A / g, it still retained a reversible capacity of 1591.7mAh / g, and the capacity retention rate was 80.3%.

[0072] Example 4

[0073] This example provides a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries and its application. The difference between this method and Example 1 is that in step (4), the silicic acid precipitate and the silicon element are mixed in a molar ratio of 1:1.2, and the other operations and parameters are the same as those in Example 1.

[0074] (1) The collected waste silicon-carbon negative electrode material and the flaky sodium hydroxide solid are uniformly mixed in a mass ratio of 5:5, and calcined at high temperature in a carbon dioxide atmosphere at a calcination temperature of 600° C. for 4 hours to obtain a calcined mixture.

[0075] (2) The calcined mixture is washed with deionized water for multiple times at a liquid-to-solid ratio of 5:1 until it becomes neutral, and then filtered to obtain a graphite material for sintering to prepare a negative electrode material for a lithium-ion battery and a silicon-containing leaching solution.

[0076] (3) The pH value of the silicon-containing leaching solution was adjusted to 1.5 with 1 mol / L sulfuric acid solution, and the reaction temperature was 80°C to completely precipitate the silicate. The silicic acid precipitate was obtained by suction filtration and dried.

[0077] (4) The silicic acid precipitate and silicon element are mixed evenly in a 1:1 molar ratio, ground into micrometer-sized powder, and calcined under vacuum conditions at a calcination temperature of 1600° C. for 4 hours. The generated gas is collected and cooled to obtain silicon dioxide solid.

[0078] (5) The silicon dioxide solid and the graphite material in step b) are subjected to carbon coating treatment, the silicon dioxide solid and the graphite material are mixed evenly in a mass ratio of 10:1.2, ground into micrometer-level powder, sintered in a CVD atmosphere furnace at a calcination temperature of 1200° C. for 10 h, and after the sintered product is naturally cooled to room temperature, it is sieved through a 300-mesh sieve to obtain a recycled product SiOx@C material.

[0079] The regenerated SiOx@C silicon-carbon electrode is used as the working electrode, the metal lithium is used as the negative electrode, and the conductive agent, the binder, the electrolyte (1 mol / L LiPF 6Dissolved in a 1:1:1 EC:DEC:DMC solvent) and a 2500-type separator were assembled into a button-type simulated battery in an argon-filled glove box (O 2 <0.01ppm, H 2 O<0.01ppm), constant current charge and discharge mode was used, and the cut-off voltage was 0.01-2.00V for electrochemical performance testing. The first reversible capacity of the material was 2138.5mAh / g. After 300 cycles at a current density of 1.0A / g, it still retained a reversible capacity of 1925.3mAh / g, and the capacity retention rate was 90.03%.

[0080] Example 5

[0081] This example provides a method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries and its application. The difference between this method and Example 1 is that the only difference is that in step (5), the silicon dioxide solid and the graphite material are evenly mixed in a mass ratio of 10:1, and the other operations and parameters are the same as those in Example 1.

[0082] (1) The collected waste silicon-carbon negative electrode material and the flaky sodium hydroxide solid are uniformly mixed in a mass ratio of 5:5, and calcined at high temperature in a carbon dioxide atmosphere at a calcination temperature of 600° C. for 4 hours to obtain a calcined mixture.

[0083] (2) The calcined mixture is washed with deionized water for multiple times at a liquid-to-solid ratio of 5:1 until it becomes neutral, and then filtered to obtain a graphite material for sintering to prepare a negative electrode material for a lithium-ion battery and a silicon-containing leaching solution.

[0084] (3) The pH value of the silicon-containing leaching solution was adjusted to 1.5 with 1 mol / L sulfuric acid solution, and the reaction temperature was 80°C to completely precipitate the silicate. The silicic acid precipitate was obtained by suction filtration and dried.

[0085] (4) The silicic acid precipitate and silicon element are mixed evenly in a 1:1 molar ratio, ground into micrometer-sized powder, and calcined under vacuum conditions at a calcination temperature of 1000° C. for 4 hours. The generated gas is collected and cooled to obtain silicon dioxide solid.

[0086] (5) The silicon dioxide solid and the graphite material in step b) are subjected to carbon coating treatment, the silicon dioxide solid and the graphite material are mixed evenly in a mass ratio of 10:1, ground into micrometer-level powder, sintered in a CVD atmosphere furnace at a calcination temperature of 1200° C. for 10 h, and after the sintered product is naturally cooled to room temperature, it is sieved through a 300-mesh sieve to obtain a recycled product SiOx@C material.

[0087] The regenerated SiOx@C silicon-carbon electrode is used as the working electrode, the metal lithium is used as the negative electrode, and the conductive agent, the binder, the electrolyte (1 mol / L LiPF6 Dissolved in a 1:1:1 EC:DEC:DMC solvent) and a 2500-type separator were assembled into a button-type simulated battery in an argon-filled glove box (O 2 <0.01ppm, H 2 O<0.01ppm), constant current charge and discharge mode was used, and the cut-off voltage was 0.01-2.00V for electrochemical performance testing. The first reversible capacity of the material was 2075.6mAh / g. After 300 cycles at a current density of 1.0A / g, it still retained a reversible capacity of 1830.3mAh / g, and the capacity retention rate was 88.2%.

[0088] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries, characterized in that: The steps include: S1. Mixing the silicon-carbon negative electrode material of waste lithium-ion batteries with an alkaline substance, and calcining the mixture in a non-oxidizing atmosphere to obtain a calcined mixture; S2, washing the calcined mixture until it is neutral, and separating the solid from the liquid to obtain a graphite material and a silicon-containing solution; S3, adjusting the pH of the silicon-containing solution to a level that causes silicate precipitation, reacting under heating, separating the solid from the liquid, and collecting the silicic acid precipitate; S4, mixing the silicic acid precipitate with silicon element, grinding them into micrometer-sized powder, calcining them under vacuum conditions, and collecting the generated silicon oxide; S5. Carbon-coating the silicon monoxide and the graphite material obtained in step S2 to obtain a regenerated silicon-carbon negative electrode material.

2. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: The alkaline substance in step S1 includes at least one of an alkali metal base or an alkali metal carbonate; preferably, the alkaline substance in step S1 includes at least one of sodium hydroxide, lithium hydroxide or sodium carbonate.

3. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: In the step S1, the mass ratio of the silicon-carbon negative electrode material of the waste lithium-ion battery to the alkaline substance is 5:1 to 5:

6.

4. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: The non-oxidizing atmosphere includes at least one of carbon dioxide, nitrogen or an inert gas.

5. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: In the step S1, the calcination temperature is 300° C. to 700° C.; and / or the calcination time is 4 to 5 hours.

6. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: In the step S3, the pH is adjusted to 1.5-3.

0.

7. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: The heating temperature in step S3 is 70-90°C.

8. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: In the step S4, the calcination temperature is 1200-1800° C.; and / or the calcination time is 4-5 hours.

9. The method for regenerating silicon-carbon negative electrode materials of waste lithium-ion batteries according to claim 1, characterized in that: In the step S5, the carbon coating treatment operation includes sintering, and the sintering conditions include at least one of the following conditions: 1) The silicon oxide and the graphite material are mixed in a mass ratio of 10:1 to 10:1.4; 2) Sintering in a CVD atmosphere furnace; 3) The sintering temperature is 1000-1200°C; 4) The sintering time is 8 to 10 hours.

10. Use of the method according to any one of claims 1 to 9 in preparing lithium ion batteries.

Citation Information

Patent Citations

  • Method for recycling positive-negative electrode mixed material of waste ternary lithium-ion battery

    CN111129632A

  • Silicon-carbon negative electrode material recovered and repaired from waste lithium ion battery as well as method and application of silicon-carbon negative electrode material

    CN117361541A

  • Graphite negative electrode active material prepared by desiliconizing regeneration of waste silicon-carbon negative electrode material as well as preparation method and application of graphite negative electrode active material

    CN117438577A

  • Silicon carbon composite material and preparation method and application thereof

    US20230286808A1

  • Lithium-ion battery

    WO2024104100A1

Cited By

  • Regeneration method for silicon-carbon negative electrode material of spent lithium-ion battery and use thereof

    WO2026138089A1